Pasting and physical properties of green banana flours and pastas - Cheok, Choon Yoong; Sulaiman, Rabiha; Manan, N. A.; Zakora, A. J.; Chin, Nyuk Ling; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Viscosity and physical properties of flours and pastas prepared from four cultivars of green bananas (namely Pisang Berangan, Pisang Nangka, Pisang Tanduk, and Pisang Nipah) have been evaluated. The moisture content and water activity of banana flours were found in the range of 7.71%-8.50% wet basis and 0.33-0.37, respectively. The peak viscosity of banana flours were observed in the order of Pisang Tanduk > Pisang Nipah > Pisang Nangka > Pisang Berangan. The water activity and colour of pastas prepared from banana flours were lower and darker compared to wheat pasta. The firmness of banana flour dried pastas were observed significantly higher than wheat pasta, with Pisang Berangan pasta recorded the highest value of 446.53 ± 7.44 g. Among the green banana cultivars, pastas prepared from Pisang Nipah and Pisang Nangka flours are recommended for consumer who is preferred of bright colour and firm texture cooked pastas.